2011
DOI: 10.1143/apex.4.063001
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Torque Diode Measurements of MgO-Based Magnetic Tunnel Junctions with Asymmetric Electrodes

Abstract: We present a detailed study of the spin-torque diode effect in CoFeB/MgO/CoFe/NiFe magnetic tunnel junctions. From the evolution of the resonance frequency with magnetic field at different angles, we clearly identify the free-layer mode and find an excellent agreement with simulations by taking into account several terms for magnetic anisotropy. Moreover, we demonstrate the large contribution of the out-of-plane torque in our junctions with asymmetric electrodes compared to the in-plane torque. Consequently, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The current dependence of T OOP is generally more complex than T IP . While T OOP is practically zero in metallic spin-valves, it can reach 40 % of T IP in magnetic tunnel junctions [14].…”
Section: Spin-torque Basicsmentioning
confidence: 98%
“…The current dependence of T OOP is generally more complex than T IP . While T OOP is practically zero in metallic spin-valves, it can reach 40 % of T IP in magnetic tunnel junctions [14].…”
Section: Spin-torque Basicsmentioning
confidence: 98%
“…Especially, it has been shown that the shape of τ ⊥ (V ) curves can change from quadratic to linear. 25,26 However, such effects were only measured in asymmetric MTJs with different FL and RL electrodes. In our junctions, the composition and thickness of the CoFeB electrodes are the same.…”
Section: B Torques and Torkancesmentioning
confidence: 99%
“…(1) is the normalised spin transfer torque term. We neglected the out plane spin transfer torque due to the non-magnetic spacer is a metal 30 .…”
Section: Lifshitz-slonczewski Equationmentioning
confidence: 99%